COMPARISON OF DIRECT COSTS OF DABIGATRAN AND WARFARIN THERAPY IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION DURING PREPARATION FOR ELECTIVE CARDIOVERSION IN THE REAL CLINICAL PRACTICE - L. E. Kuvshinova; N. V. Furman; P. V. Dolotovskaya; Ya. P. Dovgalevsky (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To compare direct medical costs of dabigatran and warfarin therapy in patients with non-valvular atrial fibrillation (NVAF) during preparation for elective cardioversion. Material and methods. An open non-randomized study was conducted to evaluate direct medical costs (cost of drug, cost of the international normalized ratio (INR) adjust- ment in outpatient clinic, cost of visits to cardiologist). Patients (n=62) with persistent NVAF (AF paroxysm duration > 48 hours) were enrolled. All of them requested medical as- sistance and were decided to perform an elective cardioversion. The patients received warfarin (n=32) or dabigatran (n=30). The patients of the both groups were similar in the main clinical characteristics and thromboembolic risk levels according to CHA2DS2-VASc scale.Results. Treatment duration before elective cardioversion was 21±2 and 30.5±4.5 days for dabigatran and warfarin groups, respectively (p<0.05). Average costs of visits to cardiologists were 3,720 and 744 RUB in warfarin and dabigatran groups, respectively (p<0.05), and drug costs were 53.63 and 1,172.01 RUB, respectively (p<0.05). The costs of laboratory INR monitoring were 3,058 RUB in warfarin group. Total costs per patient were 6,831.63 and 1,916.01 RUB in warfarin and dabigatran groups, respectively (p<0.05). Conclusion. In the real clinical practice in patients with NVAF dabigatran antithromboembolic therapy substantially reduces direct medical costs in comparison with warfarin ther- apy during preparation for elective cardioversion. Dabigatran therapy reduces time from the decision of elective cardioversion and antithromboembolic therapy start to car- dioversion performance.